The GOLPH3 pathway regulates Golgi shape and function and is activated by DNA damage - Buschman, Matthew D. (Front Neurosci, 2015)
The Golgi protein GOLPH3 binds to PtdIns(4)P and MYO18A, linking the Golgi to the actin cytoskeleton. The GOLPH3 pathway is essential for vesicular trafficking from the Golgi to the plasma membrane. A side effect of GOLPH3-dependent trafficking is to generate the extended ribbon shape of the Golgi. Perturbation of the pathway results in changes to both Golgi morphology and secretion, with functional consequences for the cell. The cellular response to DNA damage provides an example of GOLPH3-mediated regulation of the Golgi. Upon DNA damage, DNA-PK phosphorylation of GOLPH3 increases binding to MYO18A, activating the GOLPH3 pathway, which consequently results in Golgi fragmentation, reduced trafficking, and enhanced cell survival. The PtdIns(4)P/GOLPH3/MYO18A/F-actin pathway provides new insight into the relationship between Golgi morphology and function, and their regulation.